2010
DOI: 10.1177/0013916510364465
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Workplace Spatial Settings and Occupant-Perceived Support for Collaboration

Abstract: The increasingly collaborative nature of knowledge-based work requires workplaces to support both dynamic interactions and concentrated work, both of which are critical for collaboration performance. Given the prevalence of open-plan settings, this requirement has created new challenges for workplace design. Therefore, an understanding of the relationship between the spatial characteristics of workplace settings and the support for collaboration that is perceived by office workers is valuable and timely. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 27 publications
5
103
0
4
Order By: Relevance
“…Obviously, good-looking surroundings may positively affect participants' level of well-being. Previous studies indicated the positive effect of good-looking workspace on employees' well-being, productivity and creativity (El-Zeiny, 2012;Hua et al, 2011;Newsham et al, 2004;Niemelä et al, 2002;Thatcher and Milner, 2012). For instance, as suggested by Larsen et al (1998), the existence of indoor plants increase the attractiveness and comfort of office environments.…”
Section: The Role Of Work Environment Design On Individual Attitude Amentioning
confidence: 96%
See 1 more Smart Citation
“…Obviously, good-looking surroundings may positively affect participants' level of well-being. Previous studies indicated the positive effect of good-looking workspace on employees' well-being, productivity and creativity (El-Zeiny, 2012;Hua et al, 2011;Newsham et al, 2004;Niemelä et al, 2002;Thatcher and Milner, 2012). For instance, as suggested by Larsen et al (1998), the existence of indoor plants increase the attractiveness and comfort of office environments.…”
Section: The Role Of Work Environment Design On Individual Attitude Amentioning
confidence: 96%
“…Previous studies from different perspectives have shown that the perceived quality of the physical work environment have influenced in employees' job perception, satisfaction, psychological stress, attitudes and overall performance (Sundstrom et al, 1994;George and Brief, 1992;McGuire and McLaren, 2009;Thatcher and Milner, 2012;Vischer, 2007;Huang et al, 2004;Hwang and Kim, 2013;O'Neill, 2010;Carlopio, 1996;Al-Anzi, 2009;Hua et al, 2011;Davis et al, 2011). Briner (2000) suggested that the nature and arrangement of designing and furnishing a place influence the frequency and type of interaction that takes place in an environment.…”
Section: The Role Of Work Environment Design On Individual Attitude Amentioning
confidence: 99%
“…Hatch, 1987;Oldham & Brass, 1979;Oldham & Rotchford, 1983;Sundstrom et al, 1980). Furthermore, recent research has focused on issues such as the relationship between office personalisation and productivity (Nieuwenhuis, Knight, Postmes, & Haslam, 2014), the impact of standing desks on creativity (Knight & Baer, 2014), and the emotions and behaviours expressed by employees in openplan offices (Ashkanasy et al, 2014 (Hua et al, 2010;McElroy & Morrow, 2010). Secondly, research on the relationship between open-plan offices and constructs related to collaboration (e.g.…”
Section: A Short History Of Research On Physical Work Environmentmentioning
confidence: 99%
“…In terms of empirical research, there has been little research that explicitly examines the relationship between open-plan offices and collaboration, particularly in the context of teams (for exceptions see Hua, Loftness, Heerwagen, & Powell, 2010;McElroy & Morrow, 2010). As Ashkanasy et al (2014) argued, most of the research on open-plan offices is focused on individual outcomes, such as performance, satisfaction, and wellbeing, rather than on group or team processes, such as collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the innovative design of workspaces has the potential to positively or negatively influence organizational culture and creative processes (Kallio et al, 2015). The transdisciplinary and collaborative nature of the work of new products and services development teams requires spaces that support both dynamic interactions or intense and focused individual work (Hua et al, 2011) and the work in a community of practice mediated by the TICs that characterize the project teams (Harvey, 2014). The connectivity and the intelligence of the place have their source in the technological environment of which the emerging part can consist of systems with visual and auditory sensors which react to the persons by restoring from their computer memory the requirements and data of the last working session of the team (Oksanen & Ståhle, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%